2007
DOI: 10.1159/000111096
|View full text |Cite
|
Sign up to set email alerts
|

Advanced Gastric Carcinoma with Signet Ring Cell Histology

Abstract: Background: Gastric signet ring cell carcinoma (SRC) is a histological type based on microscopic characteristics and not on biological behavior. This study compared the clinicopathological features and prognosis of advanced SRC with non-signet ring cell adenocarcinoma (NSRC) of the stomach. Methods: We reviewed the records of 4,759 consecutive patients diagnosed with advanced gastric adenocarcinoma who were resected surgically from 1987 to 2003. Of these, 662 patients (13.9%) had SRC and were compared with 4,0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
119
1
6

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(136 citation statements)
references
References 27 publications
10
119
1
6
Order By: Relevance
“…Consequently, SRC can be detected at an early stage. This unique depressed endoscopic feature of SRC cancer was previously reported in other studies [3,5,11]. Among patients with EGC, the SRC type was more frequently observed in younger patients and in female patients than the differentiated type (age, P \ 0.001; female gender, P = 0.003), but showed a similar prevalence compared with the undifferentiated type (P = 0.964 and P = 0.719, respectively).…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consequently, SRC can be detected at an early stage. This unique depressed endoscopic feature of SRC cancer was previously reported in other studies [3,5,11]. Among patients with EGC, the SRC type was more frequently observed in younger patients and in female patients than the differentiated type (age, P \ 0.001; female gender, P = 0.003), but showed a similar prevalence compared with the undifferentiated type (P = 0.964 and P = 0.719, respectively).…”
Section: Discussionsupporting
confidence: 82%
“…Some studies reported better 5-year survival rates in SRC than in other cell types [1,2]. However, others reported no significant differences [3] or a poorer prognosis [4][5][6]. In addition, studies that compared SRC with the other cell types in early gastric cancer (EGC) found that SRC had lower lymph node metastasis with better prognosis than other cell types and suggested endoscopic resection for the treatment of signet ring cell-type EGC patients [7].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For surface and intracellular staining, 1Â10 5 (22) was purchased from Abcam. GAGA6, GAGA6-R þ , and GAGA6-R PDX tumor cells were cultured ex vivo and treated with various inhibitors (AZD4547, 1-AKP, and H7) for 48 hours before trypsinization.…”
Section: Flow Cytometric Analysismentioning
confidence: 99%
“…1), and is often characterized by signet ring cell histology (2), as well as rapid infiltration into the stomach wall and frequent metastasis to the lymph nodes and peritoneum (3)(4)(5). These factors contribute to a worse prognosis and lower 5-year survival rates than IGC (6)(7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%